2018
DOI: 10.1161/atvbaha.118.311807
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Artery Echogenicity and Grayscale Texture Changes in HIV-Infected Individuals Receiving Low-Dose Methotrexate

Abstract: Objective We evaluated the biological effects of low-dose methotrexate (LDMTX) on 3 novel brachial artery grayscale ultrasound measures that may indicate subclinical arterial injury. Approach and Results Exploratory analysis from a clinical trial of people with HIV infection at increased cardiovascular disease risk who were randomly assigned to LDMTX (target dose 15 mg/week) or placebo. Brachial artery ultrasound grayscale median, gray level difference statistic texture contrast (GLDS-CON), and gray level te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…By contrast, in another study published in 2018, low dose methotrexate significantly lowered the CD8 + T cell count but had no effect on inflammatory markers or endothelial function 105 . However, low dose methotrexate did favourably affect specialized ultra sonography indices in the brachial artery 106 . These preliminary studies with inflammatory biomarkers as surrogate end points will hopefully lead to clinical trials on anti inflammatory treatments with cardiovascular events as end points in the population living with HIV.…”
Section: Chronic Inflammation and Immune Cell Activationmentioning
confidence: 83%
“…By contrast, in another study published in 2018, low dose methotrexate significantly lowered the CD8 + T cell count but had no effect on inflammatory markers or endothelial function 105 . However, low dose methotrexate did favourably affect specialized ultra sonography indices in the brachial artery 106 . These preliminary studies with inflammatory biomarkers as surrogate end points will hopefully lead to clinical trials on anti inflammatory treatments with cardiovascular events as end points in the population living with HIV.…”
Section: Chronic Inflammation and Immune Cell Activationmentioning
confidence: 83%
“…Similarly, in a multicentre study, our group reported no effect of low-dose methotrexate on inflammatory markers or endothelial function 80 but methotrexate did favourably affect coronary artery echogenicity, a surrogate marker of plaque composition. 81 These preliminary studies with inflammatory biomarkers as surrogate end points will hopefully lead to larger trials of anti-inflammatory treatments with CV events as end points among individuals living with HIV.…”
Section: Treating Lipids In Hiv Patientsmentioning
confidence: 99%
“…9,10,[27][28][29] We hypothesize that as BMI increases, tissue composition and arterial wall structure are altered due to inflammatory cell infiltration, which alters the echogenicity and texture features seen on an ultrasound image. 9,10,21,28,30 Ultrasound grayscale features differ based on scatterer sizes in phantoms, thus confirming that ultrasound grayscale images are representative of the medium that the sound wave is traversing. 21,30 Thus, as tissue composition and structure of the arterial wall are altered either by weight gain and changes in overall health (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…35 In our studies of brachial artery grayscale, changes with exercise and an anti-inflammatory intervention were detected within 6 months of therapy. 30…”
Section: Discussionmentioning
confidence: 99%